Psychogenic Trevors - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1989)
The clinical presentations and criteria for diagnosis of psychogenic tremor in 24 patients are reported from the Department of Neurology, Kansas University Medical Center, Kansas City, KS.